Portuguese and Brazilian national cultures, organizational culture and trust: an analysis of impacts - Lúcio Flávio Renault de Moraes; Anderson de Souza Sant’Anna; Daniela Martins Diniz; Fátima Bayma de Oliveira (Tourism & Management Studies)
The objective of this paper is to investigate the influence of trace constituents of Brazilian and Portuguese cultures on the establishment of relationships of trust. For this purpose the head office of a Portuguese multinational company and its subsidiary in Brazil were investigated, by means of research of a qualitative nature, utilizing the case study method. Regarding data collection, twelve interviews were carried out with managers drawn from both countries, based on an interview script developed from a wide-ranging review of the literature on the theme, especially that written from the anthropological perspective, as proposed by Schein (1986). The reports of the interviews gave evidence of the relevance of a more effective management of cultural artefacts, in particular greater attention to the sharing of values, in order to foster the building of stronger bonds of trust and to stimulate cultural contexts more in tune with contemporary organizational discourse.